The Entrepreneurial Society A Reform Strategy for the European Union - Elert, Niklas; Henrekson, Magnus; Sanders, Mark (International Studies in Entrepreneurship,, 2019)
This open access book builds on the European Union's (EU) Horizon 2020 project 'Financial and Institutional Reforms for an Entrepreneurial Society' (FIRES). The authors outline how Europe can move towards more inclusive, innovative and sustainable growth through reforms that will rekindle its entrepreneurial spirit. Based on decades of research and countless discussions with stakeholders, the book also features the FIRES project's full list of policy interventions and institutional reforms that can help policymakers make that agenda a reality.